The Use of The SRIKANDI Application in Employee Performance within Local Government - Liana Liana; Sri Wulandari (Journal Of Social Science (JoSS), 2026)
As more and more human activities ely on technology, especially in today’s rapidly developing era, one such dependency is the management of archives and information. This change has given rise to a new form of archives, namely digital archives, through the use of the SRIKANDI application,  with the aim of supporting the Electronic-Based Government System. However, the application’s utilization is not fully optimal due to several obstacles. Therefore, tihis study discussed obstacles in its utilization, such as network constraitnts, central servers, and limited human resource competencies. Based on the obstacles, the researcher analyze whether these obstacles affect employee performance analyze what efforts are provided by the Archives and Library Service of Cirebon Regency, as the research location. The methode used was a qualitative descriptive metode with data collection through observation, interviews, and documentation. The use of the SRIKANDI application at the Archives and Library Service of Cirebon Regency does not impact employee perfomance, but inli affects employee work comfort. Meanwhile, efforts made by the agency include guidance, training, and the temporary use conventional systems when server problems occur. These efforts ain to maintain perfomance stability and more effective and aefficient digital archive management.